Constraint Centric Scheduling Guide - Estan, Cristian; Sankaralingam, Karthikeyan; De Carli, Lorenzo; Nowatzki, Tony; Sartin-Tarm, Michael (My University, 2013)
The advent of architectures with software-exposed resources (Spatial Architectures) has created a demand for universally applicable scheduling techniques. This paper describes our generalized spatial scheduling framework, formulated with Integer Linear Programming, and specifically accomplishes two goals. First, using the ?Simple? architecture, it illustrates how to use our open-source tool to create a customized scheduler and covers problem formulation with ILP and GAMS. Second, it summarizes results on the application to three real architectures (TRIPS,DySER,PLUG), demonstrating the technique?s practicality and competitiveness with existing schedulers.
Keywords: GAMS; Integer Linear Programming; Spatial Scheduling; Spatial Architectures